Kerusakan Lingkungan Hidup Sebagai Bentuk Pelanggaran Hak Asasi Manusia - Moh Bagus; Priyo Handoko; Hendrik Kurniawan (Magister Hukum Tata Negara Pascasarjana UIN Sunan Ampel Surabaya, 2022)
This study aims to look at global legal standards that identify with ecological problems, especially the problem of natural security. The research method used is normative legal research with two main studies, namely the statutory approach and the conceptual approach. The results of the study show that the relationship between ecological law and general freedom law are interrelated and have an impact on each other, although there are many public and global instruments on natural insurance as a component of basic freedom security, there are still many ecological problems and damages. Especially for Indonesia's natural resilience, there are several government programs, one of which is the RANHAM program, planting 1,000,000 trees and efforts to local areas. Recognizing how important climate is as part of shared freedom, local areas must be more careful and pay attention to climate for resilience. Apart from the current guidelines on ecological assurance, stricter supervision and authorization is also needed to limit natural problems. Natural resilience in Indonesia must be worked on with the aim that harmony in life is more guaranteed on the grounds that the right to a proper and strong climate is the right of every individual.